Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1399-543x.2006.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokine, growth factor and counterregulatory responses to exercise in children with type 1 diabetes and healthy controls

Abstract: In children with type 1 diabetes (T1DM), altered adaptive responses to exercise (secretion of growth factors, inflammatory cytokines, and glucoregulatory mediators) may have potential implications in growth and development, early onset of disease complications, and incidence of hypoglycemia. We therefore measured a broad spectrum of exercise responses in 12 children with T1DM (seven males and five females) and 12 controls (six males / six females) aged 11-15 yr, during a 30-min exercise challenge @ 80% VO(2)ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 53 publications
7
41
1
3
Order By: Relevance
“…At the time of disease onset, IL-6 has been identified as a major contributor to the autoimmune process leading to ␤-cell destruction in animal models of T1DM (22). It remains somewhat unclear, however, whether elevated IL-6 is only present during the early stages of the disease, or if these elevations are permanent, as some, but not all reports in diabetic patients indicate a high concentration of baseline, resting IL-6 (13,17,32). Our results may provide a possible explanation for this discrepancy, as high or normal IL-6 concentrations may have been the reflection of the particular metabolic status, including prior glycemic fluctuations, of study participants at the time of sampling, rather than an intrinsic effect of diabetes per se.…”
Section: Discussionmentioning
confidence: 95%
“…At the time of disease onset, IL-6 has been identified as a major contributor to the autoimmune process leading to ␤-cell destruction in animal models of T1DM (22). It remains somewhat unclear, however, whether elevated IL-6 is only present during the early stages of the disease, or if these elevations are permanent, as some, but not all reports in diabetic patients indicate a high concentration of baseline, resting IL-6 (13,17,32). Our results may provide a possible explanation for this discrepancy, as high or normal IL-6 concentrations may have been the reflection of the particular metabolic status, including prior glycemic fluctuations, of study participants at the time of sampling, rather than an intrinsic effect of diabetes per se.…”
Section: Discussionmentioning
confidence: 95%
“…Both studies included children with a wide age range and showed that cortisol concentrations were lower in the recovery period 1 h after exercise compared to concentrations at baseline and immediately after exercise [4,29] . Salivary cortisol measurements in adolescent female tennis players after 16 weeks of training also showed a low overall output of salivary cortisol and a blunted response to awakening [30] .…”
Section: Adrenal Axismentioning
confidence: 95%
“…Intermittent high intensity exercise reduced the decline in BG during exercise in participants with T1DM [2,6]. Repeated intense sprints interrupting longer periods of moderateintensity exercise is typical of interval training which has gained in popularity for its favorable impact on cardiovascular function [7] and may simulate the type of exercise performed in many sports.…”
Section: Discussionmentioning
confidence: 99%